1996
DOI: 10.1063/1.116551
|View full text |Cite
|
Sign up to set email alerts
|

High oxygen and carbon contents in GaAs epilayers grown below a critical substrate temperature by molecular beam epitaxy

Abstract: By quantitative secondary ion mass spectroscopy (SIMS) analyses, oxygen and carbon contents in GaAs epitaxial layers grown by molecular beam epitaxy (MBE) were found to increase significantly when the growth temperature was reduced below a critical value at about 450 °C. The concentrations of oxygen and carbon in GaAs epilayers grown below the critical temperature were about 4×1017 cm−3 and 3×1016 cm−3, respectively. Meanwhile, impurity accumulation during growth interruption became faster resulting in even hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…The presence of carbon in the samples was also confirmed by secondary ion mass spectroscopy. Using a ring density of 1 × 10 10 cm –2 and assuming no carbon in the high-growth-temperature (∼ 580 °C) GaAs spacer layers, we can estimate the p-doping concentration in the capping layers (the hot and cold caps) to be approximately 1 × 10 16 and 6 × 10 16 cm –3 in samples A and B, respectively, which are of the same order of magnitude as those reported in ref .…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…The presence of carbon in the samples was also confirmed by secondary ion mass spectroscopy. Using a ring density of 1 × 10 10 cm –2 and assuming no carbon in the high-growth-temperature (∼ 580 °C) GaAs spacer layers, we can estimate the p-doping concentration in the capping layers (the hot and cold caps) to be approximately 1 × 10 16 and 6 × 10 16 cm –3 in samples A and B, respectively, which are of the same order of magnitude as those reported in ref .…”
Section: Resultssupporting
confidence: 63%
“…The introduction of a “cold cap” procedure, in which the QRs were capped at a lower growth temperature (at 430 °C) to reduce As–Sb exchange, helped to preserve the rings and improved the QR PL intensity. However, this growth temperature is much lower than the optimum for high-quality GaAs (580 °C), which results in poor quality material, which increases the background carrier concentration . In an SC, this could increase the dark current and, in turn, reduce the open-circuit voltage.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that higher temperature MBE growth of GaAs decreases the incorporation of unintentional p-dopants. 38 Therefore the lower E 0 value for Sample J may indicate less background doping, with fewer holes in the QRs, a reduced recombination rate, and thus a higher exponent than any of the other samples.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Moreover, the low-temperature growth also strongly influences the formation of GaAs, and increases the incorporation of carbon impurities. 14 This, as we shall show, can be exploited. Recombination between confined electrons and acceptor-bound holes has a number of advantages for the study of novel physical phenomena in semiconductor nanostructures.…”
mentioning
confidence: 99%